Enterprise Information Architecture (EIA): Assessment of current practices in Malaysian organizations - Abd Razak, Rafidah; Md Dahalin, Zulkhairi; Dahari@Damiri, Rohaya; Kamaruddin, Siti Sakira; Abdullah, Sahadah (IEEE Computer Society, 2007)
In this paper we described the findings based on a research study on current Enterprise Information Architecture (EIA) practices in Malaysian organizations. Ten organizations from public and private sectors were chosen for case study analysis. The Zachman Framework was chosen as a guideline to assess the current practice of EIA in these organizations. This study had successfully investigated the current practice and conditions of EIA in selected public and private organizations in Malaysia. The study found that majority of the organizations do practice some kind of enterprise information architecture either in-house or outsource to third parties.The study also found that certain aspects of the framework were not addressed at all, whilst other aspects that were addressed vary in terms of the different perspectives. This gives a general outlook of EIA implementation in the selected organizations, which could be incomplete or not adequately addressed. The study revealed a poor knowledge and understanding of EIA among the organizations though there had been efforts at implementing EIA focusing on the Data, Function and Network architectures. The study discovered gaps in the current practice and provides suggestions for organizations to consciously embark on the EIA paradigm in order to better align the whole organization to its goals. Results of this study can be used by the government and private sectors to formulate new policies and guidelines on enterprise architecture so that the enterprise’s IT adoption and information requirements fit nicely into its business strategy.